ESTIMATION AND ANALYSIS OF TURBIDITY USING SATTELITE AND HYDROCOLOR: STUDY CASE CIREBON WATERS - Haidar Dzar Al Ghifari, Khalid
Turbidity is an optical property of water that measures the reduction in light intensity in the water column. Cirebon City is one of the fisheries centers in Indonesia which has a composition of 20 species of fish and changes in turbidity can result in a decrease in fish composition, a decrease in the level of primary productivity of the waters and fish’s ability to eat. Field survey was conducted to obtain observational turbidity and HydroColor data. HydroColor is a mobile application that can be used to obtain turbidity data. In addition, Landsat 8 OLI imagery was used to obtain the distribution of water turbidity. The purpose of this research is to estimate the turbidity using HydroColor application and satellite imagery, as well as to analyze the spatial distribution and temporal variation of the turbidity of Cirebon waters. Observation and HydroColor data were collected on September 6, 2020, while the satellite data used was Landsat 8 OLI imagery in 2020. HydroColor has estimated the turbidity of Cirebon Waters and has a fairly good correlation value with the observation data, which is 0.55. While the Landsat 8 OLI satellite imagery has estimated the turbidity of the waters using an algorithm that utilizes band 4 (B4) with a correlation value of 0.71, ????2 of 0.50 and RMSE value of 0.38. The algorithm used is: Turbidity = 90.135×B4-0.2683. High turbidity in Cirebon waters is distributed in coastal areas and river mouths, while sea areas tend to have lowest turbidity. Areas that are shaped like headlands tend to have high turbidity which is distributed further out to sea. Rainfall has a major role in influencing turbidity variations in the river mouth area with a correlation of 0.50, while wave height has a large role in influencing turbidity variations in the sea area with a correlation of 0.41. The rainy season (DJF) has the highest average turbidity, while the transitional season 2 (SON) has the lowest turbidity.